Impact of COVID-19 lockdown on the behavior change of cyclists in Lisbon, using multinomial logit regression analysis. (June 2022) - Costa, Miguel; Félix, Rosa; Marques, Manuel; Moura, Filipe
Abstract: The 2019 novel coronavirus outbreak hit most countries and cities globally, dramatically impacting how people live during lockdown periods. Compulsorily, socioeconomic activities and mobility patterns changed while long-lasting structural changes might remain. Focusing on this very particular liminal event, this paper aims to present and analyze the impact of the SARS-CoV-2 virus lockdown on the behavior change of cyclists and previously non-cyclists in Lisbon, Portugal, knowing that no concomitant interventions occurred in the cycling environment during the period analyzed (e.g., pop-up interventions). From a 1-min questionnaire in 5 locations in Lisbon's existing cycling lanes, we aimed to collect (n = 493) revealed preferences on cycling frequency before and after the lockdown, which we used to calibrate a weighted multinomial logit model to analyze respondents' probability of increasing, maintaining, or decreasing their cycling frequency. Results suggest that people tended to cycle more often after the lockdown than before. For every five cyclists, two cycled more frequently while two others maintained their cycling frequency. Most cycling trips were recreational or to exercise, and these increased after the lockdown, while trips for work and school decreased, as expected. Moreover, the lower the individuals' cycling frequency levels before the lockdown, the more they cycled after it. Our study diagnoses the impact of the lockdown on cycling habits, indicating an overall propensity to cycling more by the Lisbon citizens. Hence, authorities need to act and make quick infrastructural changes (e.g., pop-up cycling lanes) and encourage the population to use more bikes (e.g., financial incentives for bike purchases). Highlights: COVID19 virus lockdown impacts are analyzed in cyclists' behavior shifts in Lisbon. A 1-min survey captured cyclists' characteristics pre and post covid issued lockdown. 2 in 5 cyclists cycled more often while 2 in 5 kept their cycling frequency. Cycling trips which increased the most were for recreational or exercise purposes. Lower cycling frequency pre-lockdown was linked with higher levels post-confinment.